2006
DOI: 10.1021/jo052640w
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Assembly of Carbamoyl-Substituted Heteroannelated [1,4]Thiazepines

Abstract: We present a convenient synthesis of novel heteroaryl-fused 3-oxo-1,4-thiazepine-5-carboxamides and 5-oxo-1,4-thiazepine-3-carboxamides using a modification of four-component Ugi condensation. We demonstrate the usefulness and versatility of the developed approach for the synthesis of variously substituted compounds and discuss the scope and limitations of the chemistry involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Notable examples include: i) Groebke reaction of 2-aminoazines and azoles, 3,4 ii) ring-forming Ugi-type reactions of various aldehydo and keto acids, 5,6 iii) aqueous-phase b-lactam synthesis from b-amino acids, 7 and many others.…”
mentioning
confidence: 99%
“…Notable examples include: i) Groebke reaction of 2-aminoazines and azoles, 3,4 ii) ring-forming Ugi-type reactions of various aldehydo and keto acids, 5,6 iii) aqueous-phase b-lactam synthesis from b-amino acids, 7 and many others.…”
mentioning
confidence: 99%
“…Compounds 4a – c were engaged in intramolecular Ugi4‐CRs – based on the optimized conditions developed by Ivachtchenko et al for the synthesis of thiazepines starting from oxo acids7b – with a variety of isocyanides and primary amines (Figure 2). We were pleased to observe that the reactions occur smoothly without any protecting group on the indole moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Anderson et al [69] reported that one-pot condensation of 4 with Na 2 S 9 H 2 O and propan-2-amine (156) or 2,5-dimethylhexane-2,5-diamine (157) On the other hand, Ilyn et al [73] Reported that reaction of 4 with disodium thioacetate 176 in methanol afforded the corresponding acid 177, which condensed with various amines 178 and isocyanides 179 in methanol to form heteroaryl-fused derivatives of 3-oxo-1,4-thiazepine-5-carboxamides 180 (Scheme 40). 5-Allylsulfanyl-3-methyl-1-phenylpyrazole-4-carbaldehyde (182) was achieved via a one-pot reaction of allyl bromide 181, thiourea and 4 in ethanol in the presence of NaOH [70].…”
Section: Reaction With Sulfur Compoundsmentioning
confidence: 99%